Anticancer and Antibacterial Activity of Cadmium Sulfide Nanoparticles by Aspergillus niger - Mohammed S. Alsaggaf; Ashraf F. Elbaz; Sherin El Badawy-; Shaaban H. Moussa (Advances in Polymer Technology)
Cadmium-tolerant (6 mM) Aspergillus niger (RCMB 002002) biomass was challenged with aqueous cadmium chloride (1 mM) followed by sodium sulfide (9 mM) at 37°C for 96 h under shaking conditions (200 rpm), resulting in the formation of highly stable polydispersed cadmium sulfide nanoparticles (CdSNPs). Scanning electron microscopy revealed the presence of spherical particles measuring approximately 5 nm. A light scattering detector (LSD) showed that 100% of the CSNPs measure from 2.7 to 7.5 nm. Structural analyses by both powder X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) confirmed the presence of cubic CdS nanoparticles (CdSNPs) capped with fungal proteins. These CdSNPs showed emission spectra with a broad fluorescence peak at 420 nm and UV absorption onset at 430 nm that shifted to 445 nm after three months of incubation. The CdSNPs showed antimicrobial activity against E. coli, Pseudomonas vulgaris, Staphylococcus aureus, and Bacillus subtilis, and no antimicrobial activity was detected against Candida albicans. The biosynthesized CdSNPs have cytotoxic activity, with 50% inhibitory concentrations (IC50) of 190 μg mL-1 against MCF7, 246 μg mL-1 against PC3, and 149 μg mL-1 against A549 cell lines.